2006
DOI: 10.1530/rep.1.00937
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation and differential expression of neuropilin (NRP)-1 and NRP-2 genes in bovine granulosa cells

Abstract: Although much is known about the biology of vascular endothelial growth factor (VEGF) and its receptors, little is known about the role of the VEGF receptors neuropilin (NRP)-1 and NRP-2 in the process of bovine follicle development. The aim of the present study was to examine the hormonal regulation of NRP-1 and NRP-2 mRNAs by real-time PCR in follicles from the bovine ovary and in cultured granulosa cells. The NRP-1 gene was expressed in the granulosa and theca cells in the post-selection (POF) and pre-selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
1
13
0
2
Order By: Relevance
“…Moreover, Np1 expression has been shown to increase during follicular development [24] and in response to oestrogen and progesterone, but not follicle-stimulating hormone in the ovary [25]. Similarly, our studies have demonstrated that both Np1 and Np2 are involved in human wound repair, where expression is elevated early in the wound healing process, i.e.…”
Section: Neuropilinssupporting
confidence: 77%
“…Moreover, Np1 expression has been shown to increase during follicular development [24] and in response to oestrogen and progesterone, but not follicle-stimulating hormone in the ovary [25]. Similarly, our studies have demonstrated that both Np1 and Np2 are involved in human wound repair, where expression is elevated early in the wound healing process, i.e.…”
Section: Neuropilinssupporting
confidence: 77%
“…It has been reported that Acvr2a gene expression was induced by estradiol in bovine granulose cells 24) and was upregulated by noggin, which induced TGF-, TNF-, IFN-, or IL-7 in mesenchymal stem cells. 25) In this study, induction of Acvr2a gene expression ran parallel to the Th17 differentiation and regulation processes.…”
Section: Discussionmentioning
confidence: 99%
“…NRP 1, which is the most studied candidate, is a tyrosine kinase coreceptor that can bind to the membrane and is involved in angiogenic and neuronal traffic through the cytoskeleton [68]. Its expression was also reported in granulosa cells of rat and bovine species [69,70]. Keeping in mind the fact that synaptic vesicles transport was also achieved via microfilament and microtubule networks [71] and that similar cytoskeleton structures were reported in the transzonal cytoplasmic projections between CCs and the oocyte [72][73][74][75], one can assume the involvement of neuronal genes and molecules/vesicles exchange in CCs-oocyte dialogue.…”
Section: Discussionmentioning
confidence: 99%